2013
DOI: 10.7575/aiac.ijalel.v.3n.1p.170
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Beliefs about Language Learning along Gender, Further Education in Language Institutes & Different Proficiency Levels

Abstract: The aim of the present study was to understand the beliefs of Iranian EFL learners' about language learning. This study was an attempt to understand if there was any relationship between gender, proficiency level and further education in language institutes on beliefs about language learning. Accordingly, 369 EFL engineering students studying in Azad University of Tabriz, Iran were selected based on random sampling. Data were collected using two questionnaires: a demographical questionnaire, and the Beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(19 reference statements)
0
5
1
Order By: Relevance
“…These findings are consistent with previous research in which no gender difference in beliefs was reported (Tercanlioglu, 2005). In contrast, these results vary from research of Nahavandi and Mukundan (2014) who reported that on the basis of gender and proficiency levels, the significant differences was determined in engineering Iranian students' beliefs. Iqbal and Yongbing (2017) researched learner beliefs and variation on the basis of gender differences.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with previous research in which no gender difference in beliefs was reported (Tercanlioglu, 2005). In contrast, these results vary from research of Nahavandi and Mukundan (2014) who reported that on the basis of gender and proficiency levels, the significant differences was determined in engineering Iranian students' beliefs. Iqbal and Yongbing (2017) researched learner beliefs and variation on the basis of gender differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Hou, 2013), gender and learners' beliefs (e.g. Siebert, 2003;Bernatt & Lloyd, 2007;Daif-Allah, 2012;Nahavandi, 2014), language proficiency and learner beliefs (e.g. Samimy & Lee, 1997;Abedini et al, 2011;Bagherzadeh, 2012), success and learners' beliefs (e.g.…”
Section: Flourishing Creativity and Literacymentioning
confidence: 99%
“…In Iran. Nahavandi and Mukundan (2014) administered a translated Farsi version of the BALLI along with a demographic questionnaire to 369 Iranian EFL learners in Azad University of Tabriz, Iran. The participants' ages ranged from 18 to 41.…”
Section: Language Learning Beliefs and Gender Dynamics Of University mentioning
confidence: 99%